2016
DOI: 10.1038/mp.2016.163
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STEP61 ameliorates deficits in mouse and hiPSC-based schizophrenia models

Abstract: The brain-specific tyrosine phosphatase, STEP (STriatal-Enriched protein tyrosine Phosphatase) is an important regulator of synaptic function. STEP normally opposes synaptic strengthening by increasing N-methyl D-aspartate glutamate receptors (NMDARs) internalization through dephosphorylation of GluN2B and inactivation of the kinases ERK1/2 and Fyn. Here we show that STEP61 is elevated in the cortex in the Nrg1+/− knockout mouse model of SZ. Genetic reduction or pharmacological inhibition of STEP prevents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 57 publications
(107 reference statements)
3
40
0
Order By: Relevance
“…Another iPSC‐studied synapse‐regulating protein is striatal‐enriched protein tyrosine phosphatase (STEP), which acts to increase NMDAR internalization through dephosphorylating GluN2B and ERK1/2 to baffle synaptic potentiation. Xu et al recently reported that STEP 61 , one isoform of STEP, was elevated in SCZD patient iPSC‐derived forebrain neurons and induced excitatory neurons, which is consistent with their observation in the cortical lysates of the Nrg1 +/− mouse model of SCZD. Treating the iPSC‐derived neurons with neuroleptics would inhibit STEP activity, which consequently increased the phosphorylation of GluN2B and ERK1/2.…”
Section: Research Of Sczd Based On Ipsc Modelssupporting
confidence: 74%
“…Another iPSC‐studied synapse‐regulating protein is striatal‐enriched protein tyrosine phosphatase (STEP), which acts to increase NMDAR internalization through dephosphorylating GluN2B and ERK1/2 to baffle synaptic potentiation. Xu et al recently reported that STEP 61 , one isoform of STEP, was elevated in SCZD patient iPSC‐derived forebrain neurons and induced excitatory neurons, which is consistent with their observation in the cortical lysates of the Nrg1 +/− mouse model of SCZD. Treating the iPSC‐derived neurons with neuroleptics would inhibit STEP activity, which consequently increased the phosphorylation of GluN2B and ERK1/2.…”
Section: Research Of Sczd Based On Ipsc Modelssupporting
confidence: 74%
“…In vivo TC-2153 administration caused increased ERK1/2 and Pyk2 phosphorylation only in brain tissues expressing STEP, and improved novel object recognition and reference memory in the 3xTg-AD model. TC-2153 treatment also improved cognitive and motor function in the phencyclidine-induced mouse model of schizophrenia[34]. …”
Section: Trends In Small-molecule Ptp Inhibitor Developmentmentioning
confidence: 99%
“…There, PP2A functionally associates with NR3 subunit‐containing NMDAR complexes . PP2A dissociates in a catalytically inactive state from these particular complexes following NMDAR activation (Fig. ).…”
Section: Physiological Significance Of Pp2a‐dependent Tau Regulationmentioning
confidence: 99%